FINITE ELEMENT ANALYSIS OF BOND BEHAVIOR IN CORRODED REINFORCED CONCRETE BEAMS: STATE-OF-THE-ART - Y M , Arunkumar; Prashanth, Shreelaxmi; Pandit, Poornachandra; M G , Girish; Shetty , Amogh (Journal of Applied Engineering Science, 2023)
The article conducts a comprehensive examination of various aspects related to rebar corrosion, encompassing the corrosion mechanism, its implications on design criteria, the modeling of bond interfaces under both corroded and non-corroded conditions, and the modeling of reinforced concrete (RC) beams affected by corrosion, employing both empirical and analytical methodologies. The initial stages of corrosion instigate a gradual transformation of rebar into rust. One notable consequence of reinforcement corrosion is the generation of expansive pressure, leading to concrete cracking, spalling, and detachment of the concrete cover. Additionally, it diminishes the effective cross-sectional area of the rebar, ultimately resulting in a decline in the concrete's bond strength and gradual structural deterioration. Ultimately, continuous corrosion can lead to a complete loss of bond between the concrete and rebar, representing the most severe form of damage attributable to corrosion. This poses a critical threat, particularly in cases where the beam functions as an unreinforced structure, potentially culminating in sudden structural failure. This paper primarily underscores the utilization of the Finite Element Method (FEM) for evaluating the impact of bond deterioration between concrete and reinforcement caused by corrosion. The paper effectively employs this technique to predict and analyze the structural damage in corroded RC beam specimens.
Keywords: corrosion, bond modeling, RC beams, finite element method